Strategi Pengembangan BUMDes Hamu Eti dalam Rangka Peningkatan Kesejahteraan Masyarakat Desa Mondu Kecamatan Kanatang Kabupaten Sumba Timur - Caesilia Shania Djie Gesi; Jacob Wadu; Belandina L. Long; Maria M. Lino (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the development strategy of Village-Owned Enterprises (BUMDes) Hamu Eti in improving community welfare in Mondu Village, Kanatang District, East Sumba Regency. The research employs a qualitative approach using a case study method through observation, interviews, and documentation techniques. Data were analyzed descriptively using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. The results indicate that BUMDes Hamu Eti has strengths in market potential, supporting facilities, and structured organizational management. However, it faces weaknesses such as low participation, ineffective marketing, low community awareness in payment compliance, and unintegrated financial systems. Opportunities include tourism potential, third-party partnerships, and government support, while threats involve business competition, cooperative institutions, and fluctuating feed prices and tourist visits. The recommended strategies include aggressive, corrective, competitive, and defensive approaches, prioritizing institutional strengthening and human resource capacity development.